The Influence Of Net Profit Margin, Return On Assets, And Earnings Per Share On Stock Prices At PT HM Sampoerna TBK - Nofiana, Lina (Sean Institute, 2025)
This study aims to determine the effect of Net Profit Margin, Return on Assets, and Earnings Per Share on stock prices at PT HM Sampoerna Tbk, both partially and simultaneously. The independent variables in this study are Net Profit Margin, Return on Assets, and Earnings Per Share, while the dependent variable is stock price. The research uses a descriptive method with quantitative data, and the data source is secondary data. The population of this study includes financial statements from PT HM Sampoerna Tbk. The sample was determined using financial statements, including income statements and balance sheets, from the period under review. The analytical method applied is multiple linear regression analysis, with data analysis conducted using the SPSS software application. The results of the study indicate that, partially, Net Profit Margin does not have a significant effect on stock prices, as the statistical analysis shows the t-value is below the critical value, and the significance level exceeds the acceptable threshold. Similarly, Return on Assets does not have a significant impact, as its t-value is below the critical value, and the significance level is greater than the threshold. For Earnings Per Share, the analysis also shows no significant effect, as the t-value is lower than the critical value, and the significance level is above the threshold. Simultaneously, Net Profit Margin, Return on Assets, and Earnings Per Share collectively do not have a significant effect on stock prices, as the F-value is below the critical value, and the significance level exceeds the threshold.